Digitalizing of power system - Muhammad Su'aidi Dono (2019)
This report is about the author’s final year report on the topic of digitalizing the power system. Specifically, the aim is to digitalize the microgrid system to increase automation, improve efficiency, reducing operation and maintenance, and system optimization. This report presents the literature review on various topic. Literature review include key technology for data gathering, data storage, data sharing, control infrastructure, Internet-of-things technology, and example of small scale microgrid. Author also review the communication infrastructure as it is fundamentally important to optimize communication between terminal and data centers. Notable technology is smart sensors as it is becoming more intelligent and also able to handle more functions. The author will also review the concept of smart grid and microgrid to get a basis understanding of the different type of power system. Lastly the author explore a simple design for a micro grid system.